2004
DOI: 10.1080/14767050410001668671
|View full text |Cite
|
Sign up to set email alerts
|

Serial assessment of amniotic fluid index in uncomplicated term pregnancies: prognostic value of amniotic fluid reduction

Abstract: A sonographic diagnosis of oligohydramnios carries an increased risk of adverse perinatal outcome, even in low-risk pregnancies after 40 weeks. The trend in amniotic fluid volume reduction does not seem to have prognostic significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 6 publications
4
31
0
Order By: Relevance
“…Some authors [1][2][3][4] state that such pregnancies are at an increased risk of adverse perinatal outcome such as fetal distress in labor, induction of labor, cesarean delivery for fetal distress, meconium passage, low Apgar score and neonatal resuscitation or neonatal intensive care unit admission. But others [5][6][7][8] have not confirmed the association of adverse perinatal outcome with oligohydramnios; Instead they state that isolated oligohydramnios is not associated with adverse perinatal outcome. The objective of this study was to determine the association of isolated oligohydramnios at term with adverse perinatal outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors [1][2][3][4] state that such pregnancies are at an increased risk of adverse perinatal outcome such as fetal distress in labor, induction of labor, cesarean delivery for fetal distress, meconium passage, low Apgar score and neonatal resuscitation or neonatal intensive care unit admission. But others [5][6][7][8] have not confirmed the association of adverse perinatal outcome with oligohydramnios; Instead they state that isolated oligohydramnios is not associated with adverse perinatal outcome. The objective of this study was to determine the association of isolated oligohydramnios at term with adverse perinatal outcome.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Thus this study is conducted to find out the value of oligohydramnios in perinatal outcome and maternal outcome in pregnancies beyond 37 completed weeks.…”
Section: Introductionmentioning
confidence: 99%
“…1 Some studies show that amniotic fluid index is a poor predictor of adverse outcome [2][3][4][5] and some authors have not confirmed the association of adverse perinatal outcome with oligohydramnios. [6][7][8][9] Thus this study is conducted to find out the value of oligohydramnios in perinatal outcome and maternal outcome in pregnancies beyond 37 completed weeks.…”
mentioning
confidence: 99%